Multidisciplinary Rehabilitation for Chronic Widespread Musculoskeletal Pain: Results from Daily Practice. (11th June 2014) - Koele, Robin; Volker, Gerard; van Vree, Félicie; van Gestel, Marc; Köke, Albère; Vliet Vlieland, Theodora
Abstract Introduction Evidence for the efficacy of a multi‐component approach for chronic widespread musculoskeletal pain (CWP) has been reported, although the effects are overall moderate and this approach has rarely been investigated in real life. Aim The aim of the study was to describe the effects of a 15‐week multidisciplinary pain rehabilitation programme on pain, activities and participation in patients with CWP. Methods The current retrospective study used data which were routinely gathered on all consecutive patients with CWP referred to a rehabilitation programme over a 21‐month period. The 15‐week multidisciplinary rehabilitation programme consisted of cognitive behavioural therapy and exercise, as well as individual and group sessions with additional treatment modalities. Assessments included the Pain Disability Index (PDI), the Pain Catastrophizing Scale (PCS), the Multidimensional Pain Inventory (MPI), numerical scales for pain and fatigue, the Canadian Occupational Performance Measure (COPM), the one‐minute stair‐climb test and the RAND‐36. Paired t‐tests and Wilcoxon signed‐rank tests were carried out to analyse changes over time. Results A total of 165 patients were included [mean age 44.1 (standard deviation 12.9) years], 143 (87%) women). Discharge data were available for 154 patients (93%). All outcomes showed statistically significant improvements between admission and discharge (p < 0.05), with the largest effect sizes (>1.0) observed for the COPM. A longer duration of complaints was associated with less improvement in the PDI. Discussion and conclusion In daily rehabilitation practice, a 15‐week multidisciplinary treatment programme for patients with CWP showed statistically significant improvements in pain, activities and participation over time. Future studies are needed further to substantiate the long‐term cost‐effectiveness, and to identify the patients who benefit the most. Copyright © 2014 John Wiley & Sons, Ltd.